Body Parts: A Theological Anthropology, by Michelle Voss Roberts. Fortress Press, 2017 - Sydnor, Jon Paul (Interreligious Studies and Intercultural Theology, 2020)
Body Parts: A Theological Anthropology, by Michelle Voss Roberts. Fortress Press, 2017. 228 pp. Pb., $29 USD. 978-1-5064-1856-8